Circ_0000144 acts as a miR-1178-3p decoy to promote cell malignancy and angiogenesis by increasing YWHAH expression in papillary thyroid cancer - Yinli Ma; Dan Yang; Pingan Guo (Journal of Otolaryngology - Head and Neck Surgery)
Highlights 1. Inhibition of circ_0000144 repressed malignant behaviors and angiogenesis of PTC cells in vitro. 2. Knockdown of circ_0000144 constrained PTC cell proliferation in vivo. 3. Circ_0000144 acted as a miR-1178-3p sponge. 4. YWHAH acted as a downstream target for miR-1178-3p.